The Oracle of Delphi—a molecular phylogenetic approach to Greek Cordulegaster Leach in Brewster, 1815 (Odonata: Anisoptera: Cordulegastridae) - Schneider, Thomas; Vierstraete, Andy; Ikemeyer, Dietmar; van Pelt, Gert Jan; Caspers, Max; Müller, Ole; Dumont, Henri J. (Zootaxa, 2022)
Taxonomy of the genus Cordulegaster Leach in Brewster, 1815 in Greece is not completely understood. The taxonomic status of the subspecies C. helladica buchholzi (Lohmann, 1993), C. helladica kastalia (Lohmann, 1993), and C. heros pelionensis Theischinger, 1979 was still unclear. We applied a molecular genetic approach using sequences of mitochondrial and nuclear DNA fragments—cytochrome c oxidase I (COI) and Internal Transcribed Spacer 1 (ITS1). This approach revealed that specimens presently assigned to C. heros pelionensis should be considered as conspecific to the nominate subspecific taxon making C. heros a monotypic species. Two major monophyletic lines were found within the Greek representatives of the species grouped around C. bidentata Selys, 1843: the clade of the European endemic C. bidentata and the clade composed of three species: C. helladica (Lohmann, 1993), C. buchholzi (stat. nov., raised to species level), and C. insignis Schneider, 1845. Cordulegaster helladica is restricted to the Peloponnese. Cordulegaster buchholzi is not restricted to the Cyclades as previously thought, but widespread from the Cyclades over the island Euboea to south-east mainland Greece reaching in the west near Mount Parnassos, where it hybridize with C. bidentata. Hybridization between C. bidentata and C. buchholzi was detected at the Castalian Spring, where in ancient times the Oracle of Delphi was located, and some kilometres east of the Castalian Spring. These hybrids had been formerly named C. helladica kastalia. In the case of C. insignis montandoni St. Quentin, 1971 we have investigated specimens some kilometres away from the type locality in Romania, which all revealed hybrids between C. bidentata and C. insignis. However, we do not know if specimens phenotypically looking like C. insignis from further west in the SE Balkans represent isolated population of C. insignis within the range of C. bidentata or belong to a broader hybrid zone between C. bidentata and C. insignis.